Strain diversity in Mycobacterium avium subsp. paratuberculosis-positive bovine fecal samples collected in Switzerland - Rasper-Hössinger, Melina; Biggel, Michael; Stephan, Roger; Seehusen, Frauke; Scherrer, Simone (Frontiers in Veterinary Science, 2023)
Paratuberculosis or Johne’s disease is a chronic intestinal disease in domestic and wild ruminants. It affects global dairy economy and is caused by Mycobacterium avium subsp. paratuberculosis (MAP). The objective of this study was to analyze strain diversity in MAP-positive fecal samples by using a particular single nucleotide polymorphism (SNP) distinguishing between cattle (C-) and sheep (S-) type MAP and analysis of SNPs within gyrA and gyrB genes differentiating between Types I, II, and III. Moreover, mycobacterial interspersed repetitive unit and variable-number tandem repeat (MIRU-VNTR) analysis using eight established loci was performed. A total of 90 fecal samples from diseased animals presenting diarrhea and/or weight loss, originating from 59 bovine herds across 16 cantons of Switzerland were screened by PCR for the MAP-specific F57 and IS900 genes and were further subtyped. 96.7% and 3.3% of the samples contained C- and S-type MAP, respectively. Ten INRA Nouzilly MIRU-VNTR (INMV) profiles, with a discriminatory index of 0.802, calculated based on 65 epidemiological independent genotypes, were detected: INMV 1 (33.8%), INMV 2 (23.1%), INMV 6 (16.9%), INMV 9 (9.2%), INMV 116 (4.6%), INMV 3 (3.1%), INMV 5 (3.1%) and INMV 72 (1.5%), including two novel INMV profiles, namely INMV 253 (3.1%; S-type III) and INMV 252 (1.5%; C-type). INMV 1, INMV 2, and INMV 6 comprised almost 75% of the F57- and IS900-positive samples. Typing data from 11 herds suggest that there are some herds with intra-herd diversity of genotypes. The results of this study indicate a heterogeneity of MAP in Switzerland.